2022
DOI: 10.3390/ijerph192316306
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Cessation Counseling among Dental Professionals in Saudi Arabia

Abstract: The study aimed to assess the prevalence of tobacco use among dental professionals and their attitudes and behaviors about tobacco cessation counseling in Saudi Arabia. A total of 359 male and female dental professionals participated in this cross-sectional study. A pretested self-administered questionnaire was administered among study participants by visiting dental hospitals and clinics in Saudi Arabia. In the study, 15.9% of the participants were current tobacco users and 50.4% had a tobacco user at home or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…By being aware of the harmful effects of smoking and the methods of TCC, dental professionals can guide their patients toward quitting smoking and avoiding its complications. Results of the present study showed that the overall response rate among the study sample was76.2%, which is similar to other studies such as Aljubran et al 16 and Maharani et al 17 , with response rates of 77.7 and 78.45%, respectively. The study found that 23.8% of students were current smokers, primarily cigarette, which is less than the level reported in previous studies 14 , 18 .…”
Section: Discussionsupporting
confidence: 91%
“…By being aware of the harmful effects of smoking and the methods of TCC, dental professionals can guide their patients toward quitting smoking and avoiding its complications. Results of the present study showed that the overall response rate among the study sample was76.2%, which is similar to other studies such as Aljubran et al 16 and Maharani et al 17 , with response rates of 77.7 and 78.45%, respectively. The study found that 23.8% of students were current smokers, primarily cigarette, which is less than the level reported in previous studies 14 , 18 .…”
Section: Discussionsupporting
confidence: 91%